The Correlation between Mental Health and Academic Achievement among UTHM Student - Haw, Esther Li Ting; Azizan, Anim Zalina (Research in Management of Technology and Business, 2025)
Depression, anxiety, and stress are significant indicators of mental health issues, impacting careers, studies, and lives. In today’s competitive society, students face significant stress to achieve excellent grades, leading to comorbidity and loss of control over academic achievement and mental health. Malaysian students suffer from excessive stress due to cultural pressure to graduate with high scores, causing poor self-regulation and difficulty adjusting to high-level stress. The study examines the link between mental health and academic achievement among 389 undergraduate students at University of Tun Hussein Onn Malaysia (UTHM). The research, which used validated questionnaires and academic records, found a significant negative correlation between mental health and academic outcomes. Factors such as family dynamics, socioeconomic background, and access to mental health support services also influenced this relationship. The study emphasizes the need for universities to prioritize mental health awareness and implement targeted intervention programs to support student well-being. Recommendations for enhancing mental health services and creating inclusive education policies are also discussed.